Association of Osteoarthritis With Increased Risk of Cardiovascular Diseases in the Elderly: Findings From the Progetto Veneto Anziano Study Cohort. Issue 5 (27th April 2016) - Veronese, Nicola; Trevisan, Caterina; De Rui, Marina; Bolzetta, Francesco; Maggi, Stefania; Zambon, Sabina; Musacchio, Estella; Sartori, Leonardo; Perissinotto, Egle; Crepaldi, Gaetano; Manzato, Enzo; Sergi, Giuseppe
Abstract : Objective: The possible relevance of osteoarthritis (OA) as a cardiovascular disease (CVD) risk factor is still debated. The aim of this study was to investigate the association between OA and the onset of CVD in older individuals. Methods: Among a sample of 3, 099 elderly subjects, 2, 158 were identified as having no CVD at baseline and were followed up for a mean ± SD 4.4 ± 1.2 years. OA was defined using a standardized algorithm that investigated disease history, medical documentation (including radiographic reports), symptoms, and physical examination of the joints. Incident CVD was defined as the onset of coronary artery disease, heart failure, stroke/transient ischemic attack, peripheral artery disease, and CVD‐related hospitalization or mortality. Results: At baseline, 1, 336 (61.9%) of the 2, 158 study participants had OA. Participants with OA had more potential CVD risk factors, including obesity, hypertension, high levels of low‐density lipoprotein, greater severity of inflammation, and worse renal function, than did those without OA. During the follow‐up, 47.8% of the subjects with OA developed a new CVD event, compared to 41.3% of those without OA. Using an adjusted Cox regression analysis, the presence of OA significantly increased the risk of CVD (hazard ratio 1.22, 95% confidence interval 1.02–1.49; P  = 0.04). The association between OA and CVD was stronger when the hip or knee was affected, and also was stronger in women than in men and when ≥2 joints were involved. Considering single CVD outcomes, the presence of OA significantly increased the risk of new coronary artery disease, heart failure, and hospitalization for CVD. Conclusion: OA may be a significant predictor of the onset of CVD in elderly individuals, particularly in women with OA and when OA affects the lower limbs or ≥2 joints are involved.